Homesweet homegrown : how to grow, make, and store your own food, no matter where you live - Jasko, Robyn (Microcosm ; Turnaround [distributor], 2012)
A guide to sustainable living offers advice on choosing, starting, and maintaining plants; making seedling pots, composters, and a drip irrigation system; and cooking, canning, and preserving garden vegetables.